VOLCANISM AND TECTONICS ON VENUS - Nimmo F.; McKenzie D. (My University, 1998)
We review recent developments in the study of volcanism and tectonics on Venus. Venus's crust is basaltic, dry, and probably about 30 km thick. The mantle con-vects, giving rise to plumes, and has a similar composition and mean temperature (∼1300 • C), but a higher viscosity (∼10 20 Pa s), than that of the Earth. In-ferred melt generation rates constrain the lithospheric thickness to between 80 and 200 km. The elastic thickness of the lithosphere is about 30 km on aver-age. The present-day lack of plate tectonics may be due to strong faults and the high viscosity of the mantle. Most of the differences between Earth and Venus processes can be explained by the absence of water. Venus underwent a global resurfacing event 300–600 Ma ago, the cause and nature of which remains uncertain. The present-day surface heat flux on Venus is about half the likely radiogenic heat generation rate, which suggests that Venus has been heating up since the resurfacing event.